Antifungal prescribing pattern and attitude towards the treatment of oral candidiasis among dentists in Jordan - Al-Shayyab, Mohammad H.; Abu-Hammad, Osama A.; AL-Omiri, Mahmoud K.; Dar-Odeh, Najla S. (International dental journal, 2015)
Aim: The aim of this study was to evaluate the attitude of Jordanian dentists towards the treatment of oral candidiasis and their current antifungal prescribing habits, shedding more light on the possible influence of their socio-professional factors on the pattern of prescribing and practice. Methods: A structured validated questionnaire was developed and tested; it was then emailed to a random sample of 600 Jordanian dental practitioners during the period of this cross-sectional survey. The questionnaire recorded practitioners’ personal details and their attitude and prescribing of antifungal therapy for oral candidiasis. Statistical significance was based on probability values of <0.05 and was measured using the chi-square and Fisher’s exact tests. Multiple logistic regression analysis was used to analyse the influence of respondents’ socio-professional factors on their attitude towards oral candidiasis. Results: Of the 423 questionnaires returned, only 330 were included. The attitude of respondents was significantly influenced by their experience [odds ratio (OR) = 0.14; P < 0.001] and workplace (OR = 4.70; P < 0.001). Nystatin was the most commonly prescribed antifungal agent (78.2%), followed by miconazole (62.4%), which was prescribed for topical use. Systemic antifungals were prescribed by 21.2% of respondents, with a significant (P < 0.05) association with the country in which their qualification was obtained. Conclusion: The attitude towards the treatment of oral candidiasis is much better among the least-experienced dentists working in private practice. Nystatin and miconazole are the most popular choices of antifungal agents among Jordanian dentists.